Contribution of Maternal Age and Pregnancy Checkbox on Maternal Mortality Ratios in the United States, 1978-2012. Issue 2 (June 2018) - Davis, N.L.; Hoyert, D.L.; Goodman, D.A.; Hirai, A.H.; Callaghan, W.M.
Abstract : ( Am J Obstet Gynecol . 2017;217(3):352.e1–352.e7) The United States has seen a rise in the maternal mortality ratio (MMR) in the past decade, one of only 8 countries to do so. Three possible reasons for this include: an increasing maternal age and therefore increase in higher-risk pregnancies, changes in age-specific MMRs, and the inclusion of a checkbox about recent pregnancy status on death certificates. This checkbox was introduced in 2003 but was not adopted by all states, and was adopted by different states at different times, with various wording. This study aimed to assess whether the change in MMR was caused by a change in the general population or by shifts in maternal age distribution, while also assessing whether some of the increase in MMR could be attributed to the adoption of the pregnancy checkbox.